2021
DOI: 10.17159/sajs.2021/7607
|View full text |Cite
|
Sign up to set email alerts
|

Predicting take-up of home loan offers using tree-based ensemble models: A South African case study

Abstract: We investigated different take-up rates of home loans in cases in which banks offered different interest rates. If a bank can increase its take-up rates, it could possibly improve its market share. In this article, we explore empirical home loan price elasticity, the effect of loan-to-value on the responsiveness of home loan customers and whether it is possible to predict home loan take-up rates. We employed different regression models to predict take-up rates, and tree-based ensemble models (bagging and boost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The results showed that several of the machine-learning techniques predicted credit risk significantly more accurately than the industry standard of logistic regression. One specific example is a publication by Verster et al (2021) which showed that bagging and boosting techniques outperformed logistic regression when predicting take-up rates of home loans in cases where banks offered different interest rates. Meaning in the future, more machine learning techniques will be used in financial credit risk predictive modelling.…”
Section: Role and Impactmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that several of the machine-learning techniques predicted credit risk significantly more accurately than the industry standard of logistic regression. One specific example is a publication by Verster et al (2021) which showed that bagging and boosting techniques outperformed logistic regression when predicting take-up rates of home loans in cases where banks offered different interest rates. Meaning in the future, more machine learning techniques will be used in financial credit risk predictive modelling.…”
Section: Role and Impactmentioning
confidence: 99%
“…One example is ensemble-based models, such as bagging (Maldonado et al 2014), random forests (Yiu 2019), and boosting (Verster et al 2021). For all three of these ensemble machine-learning techniques (random forest, bagging, and boosting), the underlying technique is a statistical technique called CART (classification and regression tree) developed by Breiman et al (1984).…”
Section: Overlapmentioning
confidence: 99%
See 1 more Smart Citation